IMPLIKASI PERAN GANDA ISTRI TERHADAP KEHARMONISAN KELUARGA - Aeni, Ro'yal; Radjab, Safana; Masna Sholihah, Wilda; Arsyad, Maurellia Aphrodiety Arestita (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
Dual roles are two or more roles performed simultaneously, in this case, the roles refer to a woman's role as a wife to her husband, a mother to her children, and a role as a woman with a career outside the home. Family harmony is the integrity of the family, the compatibility of the relationship between husband and wife, and the presence of tranquility. The Higher School of Islamic Studies (STDI) Imam Syafi'i Jember is a Private Islamic Religious Higher Education Institution (PTKIS) that provides higher education for the Islamic generation in accordance with true religious teachings based on the Qur'an and Sunnah as understood by the companions. The purpose of this research is to analyze and find the concept of family harmony in Islam, the phenomenon of the dual roles of student wives at STDI Imam Syafi'i Jember, and the implications of the dual roles of wives on family harmony. This research uses a qualitative approach with a case study design. The results of this research show: (1) The concept of family harmony in Islam is divided into three, namely: Sakinah, mawaddah, and rahmah. (2) The phenomenon of the dual roles of student wives at STDI Imam Syafi'i Jember is indicated by helping with family finances, managing work and family, husband's support for the dual roles of wives, and challenges in facing dual roles. (3) The implications of the dual roles of wives on family harmony consist of positive and negative impacts.